Are relations between children’s hyperactive behavior, engagement, and social interactions in preschool transactional? A longitudinal study - Sjöman, Madeleine (Frontiers in Education, 2023)
Abstract Based on bioecological systems theory, engagement is the mechanism for children's learning and development. However, children with hyperactive behavior tend to be less engaged in early childhood education and care (ECEC), which might negatively influence their learning and development. On the other hand, social interaction might support children with hyperactive behavior staying engaged in these activities. The current study investigates whether the association between teacher responsiveness, positive peer-to-child interaction (i.e., the quality of peer interaction) and children's hyperactive behavior and engagement levels are transactional. Two hundred and three children aged 1 to 5 in Swedish preschool settings were followed. Data was collected at three points in time between 2012 and 2014. This data was then analysed to identify associations and how they changed over time. Transactional paths were found between children's levels of core engagement, teacher responsiveness, and the quality of positive peer-to-child interaction. Children's core engagement increases the probability of better quality positive peer-to-child interaction and teacher responsiveness, increasing core engagement over time. Teacher responsiveness and the quality of positive peer-to-child interaction are predictors of reduced hyperactive behavior over time. Meanwhile, children's hyperactive behavior does not significantly influence these two types of social interaction, that is, decreased hyperactivity may not improve social interaction to the same extent as increased engagement. The findings are discussed in relation to how special support for children with hyperactive behavior can be designed, with a focus on increasing core engagement in preschool settings.